Multimorbidity, Depression, and Mortality in Primary Care: Randomized Clinical Trial of an Evidence-Based Depression Care Management Program on Mortality Risk - Gallo, Joseph J. (J Gen Intern Med, 2015)
BACKGROUND: Two-thirds of older adults have two or more medical conditions that often take precedence over depression in primary care. OBJECTIVE: We evaluated whether evidence-based depression care management would improve the long-term mortality risk among older adults with increasing levels of medical comorbidity. DESIGN: Longitudinal analyses of the practice-randomized Prevention of Suicide in Primary Care Elderly: Collaborative Trial (PROSPECT). Twenty primary care practices randomized to intervention or usual care. PATIENTS: The sample included 1204 older primary care patients completing the Charlson Comorbidity Index (CCI) and other interview questions at baseline. INTERVENTION: For 2 years, a depression care manager worked with primary care physicians to provide algorithm-based care for depression, offering psychotherapy, increasing the antidepressant dose if indicated, and monitoring symptoms, medication adverse effects, and treatment adherence. MAIN MEASURES: Depression status based on clinical interview, CCI to evaluate medical comorbidity, and vital status at 8 years (National Death Index). KEY RESULTS: In the usual care condition, patients with the highest levels of medical comorbidity and depression were at increased risk of mortality over the course of the follow-up compared to depressed patients with minimal medical comorbidity [hazard ratio 3.02 (95 % CI, 1.32 to 8.72)]. In contrast, in intervention practices, patients with the highest level of medical comorbidity and depression compared to depressed patients with minimal medical comorbidity were not at significantly increased risk [hazard ratio 1.73 (95 % CI, 0.86 to 3.96)]. Nondepressed patients in intervention and usual care practices had similar mortality risk. CONCLUSIONS: Depression management mitigated the combined effect of multimorbidity and depression on mortality. Depression management should be integral to optimal patient care, not a secondary focus.